2013
DOI: 10.1017/s0959270913000579
|View full text |Cite
|
Sign up to set email alerts
|

The range, abundance and habitat of Hinde’s Babbler Turdoides hindei: fine-scale changes in abundance during 2000–2011 reflect temporal variation in scrub cover

Abstract: SummaryIn developing countries 'land sparing' may be more effective than 'land sharing' in partially mitigating the impacts of farming on bird species diversity. We examined the pattern of change in the global and local distribution of Hinde's Babbler Turdoides hindei, a 'Vulnerable' Kenyan endemic whose local abundance is dependent on a passive form of land sharing, in which farmland is left fallow or abandoned, enabling Lantana scrub to colonise. In 2011 we assessed the species' global range and resurveyed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that habitat or diet generalists use a broader variety of habitats and resources than specialists do and, thus, may adapt more readily to environmental changes (Devictor et al., ; Gray, Baldauf, Mayhew & Hill, ). Conversely, bird species specialized on dense habitats typically have high site fidelity and remain within their favored habitat patches (Shaw & Musina, ; Shaw, Njoroge, Otieno & Mlamba, ), as long as sufficient resources are available (Wiktander, Olsson & Nilsson, ). However, increasing habitat degradation and fragmentation might cause increased overall home‐range size in both generalist and specialist bird species (Carey et al., ; Hansbauer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that habitat or diet generalists use a broader variety of habitats and resources than specialists do and, thus, may adapt more readily to environmental changes (Devictor et al., ; Gray, Baldauf, Mayhew & Hill, ). Conversely, bird species specialized on dense habitats typically have high site fidelity and remain within their favored habitat patches (Shaw & Musina, ; Shaw, Njoroge, Otieno & Mlamba, ), as long as sufficient resources are available (Wiktander, Olsson & Nilsson, ). However, increasing habitat degradation and fragmentation might cause increased overall home‐range size in both generalist and specialist bird species (Carey et al., ; Hansbauer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The probability that locations are displayed outside a riparian thicket due to high inaccuracy of triangulation (while in reality T. hindei is inside dense thicket, see Shaw et al . 2014) is very likely. In contrast, data from spot-mapping underline restricted movement and long-term roosting in dense thickets.…”
mentioning
confidence: 98%
“…The species is a cooperative breeder and thus exists in distinct family groups differing in size (ranging between two to 10 individuals) (Shaw et al . 2014). In this study we observed four identical family groups, using spot-mapping and telemetry.…”
mentioning
confidence: 99%
See 1 more Smart Citation